Respon Stress Dalam Proses Pemulihan Covid-19: Case Study - Lailatul Hafidah; Nur Iszakiyah; Moh Jufriyanto; Prastomo Suhendro (Wiraraja Medika : Jurnal Kesehatan, 2022)
Mental health problems that increase during the pandemic include stress and anxiety. For those who are exposed to or confirmed to be positive for COVID-19, it creates its own stressor and level of anxiety. This study aims to determine the description of the stress response in the Covid-19 recovery process. This study uses a qualitative descriptive research design with a case study approach. The number of participants who participated in this study were ten employees who were exposed to Covid-19 using a purposive sampling technique. The place of this research is in the Madura State Polytechnic. Data collection was carried out using the in-depth interview method for employees who were exposed to COVID-19. The results of the study revealed that there were 3 themes, namely stress, support systems and individual coping strategies. To manage stress, anxiety, and depression, you should change your mindset, behavior and lifestyle and start fun physical activities. And it is hoped that educational institutions will monitor mental health problems for the entire academic community during the COVID-19 pandemic so that if confirmed positive, they have adaptive coping and help physical and mental recovery.